KAJIAN SOSIAL MENGENAI MASYARAKAT EKONOMI ASEAN (MEA) DI ASIA TENGGARA - Amelia Putri Aulia (Jurnal Samudra Geografi, 2023)
MEA is to maintain political stability and security in the ASEAN region, increase the competitiveness of the region as a whole in the world market, promote, reduce poverty and economic growth, and improve the living standards of the population of ASEAN member countries. Therefore, it is necessary to carry out a more in-depth analysis of the purpose of establishing the MEA in social aspects, especially in the political and economic fields of the countries in it. This study aims to find out social studies regarding the ASEAN Economic Community (AEC) in Southeast Asia. The method used is a literature study approach. The literature study was conducted by collecting various references related to the titles studied regarding globalization and its impact on the economic growth of ASEAN countries. The data from the World Bank shows the GDP in the last five years for each country in Southeast Asia. The results of the study show that there are differences between each country that experiences an increase or decrease in the country's economy.